The Synergistic Action of Electro-Fenton and White-Rot Fungi in the Degradation of Lignin - Hou, Lipeng; Ji, Dandan; Dong, Weifang; Yuan, Lin; Zhang, Fengshan; Li, Yan; Zang, Lihua (Frontiers in Bioengineering and Biotechnology, 2020)
White-rot fungus is a common lignin-degrading fungus. However, compared with those of microorganisms that biodegrade lignin alone, synergistic systems of electro-Fenton processes and white-rot fungi are superior because of their high efficiency, mild conditions, and environmental friendliness. To investigate the details of lignin degradation by a synergistic system comprising electro-Fenton processes and white-rot fungi, lignin degradation was studied at different voltages with three lignin-degrading fungi (Phanerochaete chrysosporium, Lentinula edodes, and Trametes versicolor). The lignin degradation efficiency (82∼89%) of the synergistic systems at 4 V was higher than that of a control at 96 h post inoculation. Furthermore, the H2O2 produced and phenolic lignin converted in the system can significantly enhance the efficiency of ligninolytic enzymes, so a considerably increased enzyme activity was obtained by the synergistic action of electro-Fenton processes and white-rot fungi. 13C NMR spectroscopy revealed that aromatic structure units (103–162 ppm) were effectively degraded by the three fungi. This study shows that the combination of electro-Fenton processes and white-rot fungi treatment significantly improved the lignin degradation efficiency, which established a promising strategy for lignin degradation and valorization.